Understanding Pathways To and Away From Violent Radicalization Among Resettled Somali Refugees, 4 North American cities, 2013-2015 - Ellis, Heidi ([Verlag nicht ermittelbar], 2020)
Somalis in North America offer a window into the remarkable potential that can be realized by refugees/immigrants despite experiences of severe adversity as well as the challenges some subgroups encounter when adjusting to life in a new country. Somalia has endured one of the longest and most brutal wars of the past 30 years. This enduring conflict has led to millions of Somalis being dispersed as refugees across the globe. As refugees with limited resources, many Somalis in North America are resettled in poor urban neighborhoods where they are visibly different, not only because of race or ethnicity but also because of dress, especially for women who wear a Muslim head covering. In addition, the community has been plagued by violence. While the number of Somali American youth joining these groups are small and while the majority of Somali Americans are law-abiding citizens, the terrorist groups' ability to recruit these youth and to convince some of them to engage in violent acts is concerning, not only to policymakers and law enforcement, but also to the Somali community, which fears losing more youth to violence or having the community's reputation sullied by being associated with terrorism. While some of the social and cultural factors affecting Somalis are unique to that ethnic group, they also share experiences common to many immigrants, navigating identity development and duality as they move between home and host cultures, contending with discrimination as religious, racial and ethnic minorities, and striving to achieve their dreams while struggling to gain socioeconomic stability. Thus, understanding their developmental trajectories may inform the understanding of other immigrant and refugee groups as well. No valid and reliable measurement for risk for violent extremism exists; there is no single profile or set of risk factors that can accurately determine who is most at risk for engaging in violent extremist acts. The study did not attempt to determine who is most at risk. Rather, the researchers sought to identify broad attitudes that would indicate a general openness to, or rejection of, the use of violence or illegal actions in support of a political cause. The qualitative interviews feature experiences of formal (e.g. police) and informal (e.g. community) institutions over the past year. Examples of interview prompts include questions related to social bonds with family and community, and interactions with police.